1998
DOI: 10.1097/00005768-199801000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Energy absorption of impacts during running at various stride lengths

Abstract: It was postulated that the increased perpendicular distance from the line of action of the resultant ground reaction force to the knee joint center played a role in this increased energy absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
226
4
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(260 citation statements)
references
References 19 publications
19
226
4
3
Order By: Relevance
“…Investigation on the relationship between the impact load and kinematic parameters will exhibit biomechanical reasons why the impact force and the loading rate did not increase consistently as the grade increased. It was reported in the previous studies (Nigg et al, 1995a;Gerritsen et al, 1995;Derrick et al, 1998) that the impact force and loading rate in running were affected by the kinetic energy of the whole body at the foot contact and the knee fl exion just after the foot contact. The result that the peak loading rate showed signifi cant partial correlations with Von and the time from the foot contact to peak knee fl exion velocity (TPKFV) indicates that the loading rate increased with the increase in Von and with the decrease in TPKFV regardless of the grade ( Table 2).…”
Section: Impact Force and Leg Motion In Downhill Runningmentioning
confidence: 99%
“…Investigation on the relationship between the impact load and kinematic parameters will exhibit biomechanical reasons why the impact force and the loading rate did not increase consistently as the grade increased. It was reported in the previous studies (Nigg et al, 1995a;Gerritsen et al, 1995;Derrick et al, 1998) that the impact force and loading rate in running were affected by the kinetic energy of the whole body at the foot contact and the knee fl exion just after the foot contact. The result that the peak loading rate showed signifi cant partial correlations with Von and the time from the foot contact to peak knee fl exion velocity (TPKFV) indicates that the loading rate increased with the increase in Von and with the decrease in TPKFV regardless of the grade ( Table 2).…”
Section: Impact Force and Leg Motion In Downhill Runningmentioning
confidence: 99%
“…These impacts have magnitudes up to 2.3 times body weight (BW) with an impact load rate of 113 BW.s -1 (29). Increases in impact shock can result from an increase in running speed (21), from running downhill (22), from an increase in stride length (15,23) …”
Section: Paragraph Number 22mentioning
confidence: 99%
“…For example, running 32 km.week -1 will produce over 1.3 million impacts to the body over a period of one year (16). More frequent impacts will place greater stress on the muscles, tendons and bones resulting in an increased risk of injury and degenerative disease (15). Therefore, to attenuate this risk, mechanical adjustments such as a decrease in the vertical oscillation of the CM may take place with training.…”
Section: Paragraph Number 23mentioning
confidence: 99%
“…Following this the participant was fitted with the wireless, tri-axial accelerometer (Emerald, APDM, OR, USA), used to measure accelerations (reported accuracy 0.0012 m·s 2 ·√Hz -121 ) of the distal anterolateral aspect of the right tibia, selected to minimize soft tissue oscillations during impact 21 and not infers with gait patterns during ATM running. The accelerometer was packed tightly into a waterproof sport armband housing (h 2 oaudio, San Diago, CA, USA) and secured tightly.…”
Section: Procedures and Measurementsmentioning
confidence: 99%
“…20 Importantly, it is suggested that the anatomical structures that benefit from the reduced load of ATM training are the hip, knee and foot joints along with the passive structures of the lower limbs. These normally take the strain in land based running 21,22 and are most at risk of injury amongst endurance runners.…”
Section: Introductionmentioning
confidence: 99%